Pemanfaatan Bahasa Iklan Sebagai Penunjang Media promosi di Jalan Akasia - Mirsa Umiyati (Warmadewa Press, 2020)
Warmadewa University has had a significant transformation to its surrounding which used to be agricultural land, currently this land is occupied by several traders who offer their products and services especially on Akasia street. There are differences when viewing from an economic point of view before the pandemic which has been going on for the last few months which has caused a drastic decline in turnover of traders around the Warmadewa University. Based on the visions and missions of Warmadewa University to increase the quantity and quality of the community service that is the prosperity of the traders. Then, the solutions that can be offered is to apply the method, namely the socialization of advertising languages to attract consumers through print and online media with the hope of a revival of the economy for traders in the midst of this pandemic. The results of this study prove that Community Service Activities with the target of the traders at Akasia Street have gotten better by increasing partners' knowledge in promotional strategy by applying adveritising language through print media such as distributing printed and online media such as distribution of product/service advertising banners in the form of education in the use of advertising language in social media accounts such as WhatsApp, Instagram and Facebook.